Preyssler catalyst-promoted rapid, clean, and efficient condensation reactions for 3H-1,5-benzodiazepine synthesis in solvent-free conditions - Pasquale, Gustavo Antonio (2013)
A simple, convenient, and environmentally benign synthesis of 1,5-benzodiazepines is developed by condensing different o-phenylenediamines and 1,3-aryl-1,3-propanodiones. The reaction is catalyzed by a Preyssler (NaH14P5W30O110, HPA) heteropolyacid as a safe, clean, and recyclable catalyst. The method is operationally simple and provides access to a variety of 1,5-benzodiazepines in good to excellent yields.